2005
DOI: 10.1002/jsfa.2060
|View full text |Cite
|
Sign up to set email alerts
|

Fruit load or fruit position alters response to temperature and subsequently cherry tomato quality

Abstract: Changes in fruit-source ratio during the growth and maturation of cherry tomato fruits were studied in combination with increased fruit temperature. Six treatments were compared: the presence or absence of local heating combined with different fruit origins (7P, fruit from trusses pruned to seven flowers; 14P, proximal fruits; 14D, distal fruits from trusses pruned to 14 flowers). 7P were less sensitive to heating whereas 14P and 14D showed greater reduction in water and dry matter (DM) content. Distal fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
49
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 30 publications
16
49
3
Order By: Relevance
“…7). This could be due to high fruit load at higher temperatures as suggested by Gautier et al 10 Increased fruit temperature leads to a higher transpirational flux, which in turn stimulates the translocation of nutrients to the fruit sink, thereby increasing sink strength. Increased day temperature can induce an increase in the Vit C content of tomatoes.…”
Section: Effect Of Cumulative Temperature On Tomato Qualitymentioning
confidence: 91%
See 2 more Smart Citations
“…7). This could be due to high fruit load at higher temperatures as suggested by Gautier et al 10 Increased fruit temperature leads to a higher transpirational flux, which in turn stimulates the translocation of nutrients to the fruit sink, thereby increasing sink strength. Increased day temperature can induce an increase in the Vit C content of tomatoes.…”
Section: Effect Of Cumulative Temperature On Tomato Qualitymentioning
confidence: 91%
“…Although temperature is known to affect cell wall properties responsible for fruit texture, 20 its effect on tomato firmness is still not clear. For instance, Gautier et al 10 found no change in fruit firmness as a result of a 1.1…”
Section: Effect Of Cumulative Temperature On Tomato Qualitymentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, fruit load (Do et al, 2010) and fruit position also influence quality. Tomato fruits are known to compete within a truss (Gautier et al, 2005), and greenhouse tomato producers usually prune trusses to maximize fruit growth and quality. The position of the truss on the plant has also been found to influence various metabolites in the fruits (Bénard et al, 2009), including lycopene and b-carotene (Fanasca et al, 2007), as well as seed quality (Dias et al, 2006).…”
mentioning
confidence: 99%
“…These results appear to agree with those of the present study at 24 and 29 WAT (Table 3) (Figs. 1 A and 2 A, 2B), as the decline in the lycopene content could be due to the oxidation of this compound to β-carotene; however, β-carotene degradation also intensifies from 35 to 40ºC (Rosales et al, 2006;Gautier et al, 2005).…”
Section: Antioxidant Capacity and Phytonutrientsmentioning
confidence: 99%